Ultrasound a core review - Shrestha, Ruchi; Ngan, Ka-Kei (Core review series., 2018)
"Uniquely designed for the Core Exam, Ultrasound: A Core Review covers all key aspects of ultrasound, mimicking the image-rich, multiple-choice format of the actual test. Ideal for residents getting ready for the Core Examination, as well as practitioners taking recertification exams, this one-of-a-kind review follows the structure and content of what you'll encounter on the test, effectively preparing you for Core Exam success! Key Features: Contains 300 image-rich ultrasound questions with answers, explanations, and references. Features high-quality black-and-white, color, and spectral Doppler images throughout. Covers organ-specific ultrasound as well as gynecologic, pregnancy, vascular, musculoskeletal, peritoneal space, retroperitoneum, abdominal wall, chest, and ultrasound-guided procedures. Includes questions on noninterpretive skills such as ultrasound physics and quality and safety. Provides answers and rationales as to why an answer is correct and other choices are incorrect. Your book purchase includes a complimentary download of the enhanced eBook for iOS, Android, PC & Mac. Take advantage of these practical features that will improve your eBook experience: The ability to download the eBook on multiple devices at one time -- providing a seamless reading experience online or offline. Powerful search tools and smart navigation cross-links that allow you to search within this book, or across your entire library of VitalSource eBooks. Multiple viewing options that enable you to scale images and text to any size without losing page clarity as well as responsive design. The ability to highlight text and add notes with one click."--Provided by publisher